1999
DOI: 10.1007/s004649901045
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized controlled trial of sclerotherapy vs ligation in the prophylactic treatment of high-risk esophageal varices

Abstract: EIS and EVL are similarly effective in the prevention of first variceal bleeding. The choice between EIS and EVL depends on the skill of the endoscopic unit. For highly experienced surgeons facing no complications, sclerotherapy seems to be preferable; for all others, it is technically easier to perform ligation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 19 publications
1
42
1
1
Order By: Relevance
“…To improve these EVL results, we performed additional ethanol-EIS for varices that could not be eradicated by EVL alone. Nonetheless, variceal relapse also occurred in patients treated by this method, although the relapse rate and bleeding rate of esophageal varices compared to the reported results of EVL [26][27][28][29][30][31] were lower. The present study was performed to evaluate the effect of this treatment on portal hemodynamics, and especially on portal systemic shunts, and to determine how these hemodynamic changes are associated with variceal relapse.…”
Section: Discussioncontrasting
confidence: 61%
“…To improve these EVL results, we performed additional ethanol-EIS for varices that could not be eradicated by EVL alone. Nonetheless, variceal relapse also occurred in patients treated by this method, although the relapse rate and bleeding rate of esophageal varices compared to the reported results of EVL [26][27][28][29][30][31] were lower. The present study was performed to evaluate the effect of this treatment on portal hemodynamics, and especially on portal systemic shunts, and to determine how these hemodynamic changes are associated with variceal relapse.…”
Section: Discussioncontrasting
confidence: 61%
“…This finding is similar to results from several centers where rubber band ligation was compared with injection sclerotherapy and showed that far fewer sessions were required with banding to achieve variceal obliteration [17][18][19]. The fewer sessions of banding meant fewer risks of procedure related complications.…”
Section: Ale Alexander Femi Et Al: Endoscopic Variceal Band Ligationsupporting
confidence: 77%
“…been shown to be effective in decreasing bleeding, 4,[18][19][20][21] it is associated with side effects of its own, including postligation bleeding, pain from ulceration, dysphagia, and odynophagia. 10,11,[22][23][24] Few data exist regarding adjuvant therapy for EVL or sclerotherapy.…”
Section: Discussionmentioning
confidence: 99%